Zinc - Lukaski, H. C. (Sports Nutrition, Vitamins and Trace Elements, 1997)
As people become more physically active, they inquire whether nutrient intakes are adequate to meet the needs of increased energy expenditure. Knowledge about the needs of an individual for minerals, particularly zinc, an element that is required for optimal use of dietary protein, fat and carbohydrate, is scanty. Although the information available is limited, it appears that the majority of recreational and competitive athletes consume diets that provide adequate amounts of zinc and other minerals. However, mineral intakes may be inadequate among certain groups of athletes, such as wrestlers and ballerinas, who seek to reduce body weight to meet specific body weight standards. Losses of zinc in the urine and sweat increase during and immediately after exercise but return to non-exercise values on the day after exercise. Athletes should receive nutrition counseling to emphasize proper choices of food to provide adequate amounts of minerals and other nutrients rather than rely on nutritional supplements. Use of zinc supplements is advised only under proper medical supervision to avoid the potential of adverse effects on absorption of other minerals and health. This information will be useful to nutritionists who advise people involved in all aspects of physical activity.